Additional effects of psychological interventions on subjective and objective outcomes compared with exercise-based cardiac rehabilitation alone in patients with cardiovascular disease: A systematic review and meta-analysis. (29th August 2020) - Albus, Christian; Herrmann-Lingen, Christoph; Jensen, Katrin; Hackbusch, Matthes; Münch, Nina; Kuncewicz, Catharina; Grilli, Maurizio; Schwaab, Bernhard; Rauch, Bernhard; ,
Abstract: Background: Exercise-based cardiac rehabilitation (ebCR) often includes various psychological interventions for lifestyle change or distress management. However, the additional benefit of specific psychological interventions on depression, anxiety, quality of life, cardiac morbidity and cardiovascular or total mortality is not well investigated. Design: Systematic review and meta-analysis. Methods: Randomized controlled trials and controlled cohort trials published between January 1995 and October 2017 comparing ebCR with or without pre-specified psychosocial interventions were selected and evaluated on the basis of predefined inclusion and outcome criteria. Results: Out of 15, 373 records, 20 studies were identified, including 4450 patients with coronary artery disease (88.5%) or congestive heart failure (11.5%), respectively. Studies were of low to moderate quality and methodological heterogeneity was high. As compared with ebCR alone, additional psychological interventions for lifestyle change or distress management showed a trend to reduce depressive symptoms (standardized mean difference –0.13, 95% confidence interval (CI) –0.30; 0.05). Furthermore, during a follow-up of five years, distress management was associated with a trend to reduce cardiac morbidity (risk ratio 0.74, 95% CI 0.51; 1.07). There was no evidence for an additional impact of either psychological lifestyle change interventions or distress management on anxiety, quality of life, cardiovascular or total mortality. Conclusions: Specific psychological interventions offered during ebCR may contribute to a reduction of depressive symptoms and cardiac morbidity, but there remains considerable uncertainty under which conditions these interventions exert their optimal effects. (CRD42015025920).